NEOBANKING AS A DIRECTION OF DEVELOPMENT OF MODERN FINANCIAL TECHNOLOGIES - A. V. Komarov; V. M. Martyukova (Вестник университета)
Neo-banking as one of the most important directions of development of modern financial technologies has been considered. The aim of the paper is to study the fundamental prerequisites, advantages and prospects of neobanking development in the Russian Federation. By the methods of retrospection, analysis, comparison and graphical research, characteristics of foreign and domestic neobanks, such as: Tinkoff Bank, Rocketbank, Touch Bank, Tochka have been given and also their detailed comparative analysis with traditional banking institutions is carried out. Based on the results of the study, the conclusion about the dominant role of neobanking in terms of the modern digital transformation of the world economy has been made.